2018
DOI: 10.1177/0003489418784968
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation and Contributions of National Database Studies in Otolaryngology Literature Published in the United States: 2005-2016

Abstract: There was a nearly 10-fold increase in database publications in 2016 compared to 2005. The majority provide descriptive data and outcomes measures. The role of these studies warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Subbarayan et al identified 310 studies published on various national databases between 2005 and 2016 within the otolaryngology literature alone. 21 These database studies are highly advantageous because of their inherent statistical power. 7 However, more often than not, we are confronted with myriad tables of statistics that relate to whatever clinical question is being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Subbarayan et al identified 310 studies published on various national databases between 2005 and 2016 within the otolaryngology literature alone. 21 These database studies are highly advantageous because of their inherent statistical power. 7 However, more often than not, we are confronted with myriad tables of statistics that relate to whatever clinical question is being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…An area where ML may be of additional value is in the analysis of large clinical data registries. Multi-institutional, national, and international data registries allow higher statistical power and open doors to address previously difficult-to-answer questions [27]. Due to the aforementioned strengths, a model developed using ML would be able to account for intricate interactions among variables [26].…”
Section: Discussionmentioning
confidence: 99%
“…When diseases encountered in daily practice are evaluated, otolaryngology practice is generally formed of otological and rhinological diseases. [11][12][13][14][15] In the publications from Turkey in the field of otolaryngology, the articles which were most cited were seen to be mostly otology and rhinology. 2,3 The reason for the highest number of pediatric studies was considered as the most widely accepted journal in this study was the International Journal of Pediatric Otorhinolaryngology.…”
Section: Discussionmentioning
confidence: 99%